Web-Based ICT Training to Strengthen Early Childhood Teachers’ Digital Competence in UIN Ponorogo Partner Kindergartens - Umi Rohmah; Waris Waris (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
The growing emphasis on digital transformation in education highlights the need for teachers, including those in early childhood education (ECD), to develop stronger digital competencies. This study examined the effectiveness of a web-based ICT training program designed to enhance teachers’ digital literacy, particularly in managing school websites as a medium of communication and promotion. The research employed a qualitative case study design through observation, interviews, and group discussions. The training was designed using the ADDIE model and combined theoretical input with hands-on practice in website management, including uploading news and promoting school activities online. Findings revealed significant improvements in teachers’ digital literacy, confidence, and ability to participate actively in web-based communication. Schools that had previously shown little online activity became more engaged through their websites. These outcomes support prior research that stresses the value of practical ICT training in preparing teachers for digital readiness. Nevertheless, challenges remained regarding the short training duration and disparities in participants’ digital proficiency. The study demonstrates that targeted ICT training can play a crucial role in enhancing teachers’ professional development and facilitating their adaptation to the demands of the digital era.